HARMONIOUS RHYTHMS: EXPLORING THE IMPACT OF MUSIC ON PRODUCTIVITY IN EDUCATIONAL AND WORKPLACE SETTINGS - Kalkumbe, Khushi (Proceeding of International Conference on Social Science and Humanity, 2024)
Background: The relationship between music and productivity has garnered significant interest in both educational and workplace settings, prompting investigations into the cognitive and emotional mechanisms through which music influences task performance. Specific Background: Existing literature suggests that music can enhance cognitive processes, yet findings remain inconclusive regarding its overall impact on productivity levels, particularly in relation to individual differences and environmental factors. Knowledge Gap: Limited empirical studies have simultaneously addressed how genre preferences, personality traits, and contextual variables moderate the effects of music on productivity, highlighting the need for a comprehensive examination of these interactions. Aims: This research aims to elucidate the relationship between music listening and productivity levels among students and employees by employing a mixed-methods approach, integrating quantitative surveys and qualitative interviews. Results: Preliminary findings indicate that music listening positively influences cognitive processes such as concentration and memory while also alleviating stress and anxiety, thus enhancing overall task performance. However, variations were noted based on individual music preferences and the nature of the tasks performed. Novelty: This study uniquely synthesizes insights from psychology, neuroscience, and organizational behavior to provide a nuanced understanding of how music can be effectively integrated into productivity-enhancing strategies. Implications: The results suggest that educators and employers should consider individual preferences and contextual factors when incorporating music into productivity frameworks. By fostering environments conducive to music listening and allowing flexibility in music selection, stakeholders can optimize performance and well-being, thereby promoting creativity and satisfaction in both educational and workplace settings.